A Study on Urban Regeneration Policy Change in Korea - An, Hyunjin; Song, Aeijung; Park, Hyeon-yong; Kim, Meeyoung (International Planning History Society Proceedings, 2018)
After the physical redevelopment and reconstruction in the late 1970s, the paradigm on urban regeneration in Korea shifted from maintenance to restoration and sustainability. This study highlighted that those changes occurred rapidly and not gradually over a short period of time. This study researched diachronic changes on urban regeneration policies after the 1970s in Korea using an analysing model that compensated for the theoretical limits of Hogwood and Peters. The limitations of former policies and internal and external socio-economic factors are shown to have affected dynamic policy changes. This study’s academic significance is that it suggests policy implications for cities that have similar urban growth processes to Korea.